Ibn Hazm Approach on Christianity: An Analysis to His Book al-Fiṣal fi al–Milal wa al-Ahwa wa al-Niḥal - Ahmad, Mahmud; Mohd. Khambali@Hambali, Khadijah (Jurnal Usuluddin, 2011)
Ibn Hazm al-Zahiri stood out as a critical analyst of Christian scriptures, however without giving any justification (ta’lel). Thus, his analysis methodology is known as the al- al-Zahiri Methodology. This paper seeks to introduce his methodology, analyze the approaches, his objections and critiques adopted by him in his study of Christianity. The interaction between Muslims and Christians in al-Andalus stimulated Ibn Hazm to master Christianity and its scriptures. His book al-Fisal is an outcomes of the continuous friction between Islam and Christianity in al-Andalus. Kitab al-Fisal fi al-Milal wa alAhwa wa al-Nihal continues to be considered a work of monumental significance in comparative religion, the first of its kind to systematically study of the religious doctrines of Islam, Judaism, and Christianity.